Survey on antimicrobial resistance patterns in Vibrio vulnificus and Vibrio cholerae non-O1/non-O139 in Germany reveals carbapenemase-producing Vibrio cholerae in coastal waters - Bier, Nadja; Schwartz, Keike; Guerra, Beatriz; Strauch, Eckhard (Frontiers in Microbiology, 2015)
An increase in the occurrence of potentially pathogenic Vibrio species is expected for waters in Northern Europe as a consequence of global warming. In this context, a higher incidence of Vibrio infections is predicted for the future and forecasts suggest that people visiting and living at the Baltic Sea are at particular risk. This study aimed to investigate antimicrobial resistance patterns among Vibrio vulnificus and Vibrio cholerae non-O1/non-O139 isolates that could pose a public health risk. Antimicrobial susceptibility of 141 V. vulnificus and 184 V. cholerae non-O1/non-O139 strains isolated from German coastal waters (Baltic Sea and North Sea) as well as from patients and retail seafood was assessed by broth microdilution and disk diffusion. Both species were susceptible to most of the agents tested (12 subclasses) and no multidrug-resistance was observed. Among V. vulnificus isolates, non-susceptibility was exclusively found toward aminoglycosides. In case of V. cholerae, a noticeable proportion of strains was non-susceptible to aminopenicillins and aminoglycosides. In addition, resistance toward carbapenems, quinolones, and folate pathway inhibitors was sporadically observed. Biochemical testing indicated the production of carbapenemases with unusual substrate specificity in four environmental V. cholerae strains. Most antimicrobial agents recommended for treatment of V. vulnificus and V. cholerae non-O1/non-O139 infections were found to be effective in vitro. However, the occurrence of putative carbapenemase producing V. cholerae in German coastal waters is of concern and highlights the need for systematic monitoring of antimicrobial susceptibility in potentially pathogenic Vibrio spp. in Europe.